Islam dan Kesetaraan Gender dan Penerapannya pada Masyarakat Kontemporer - Anzalman; Thaheransyah; Firdaus, Khairul; Ariani, Rina; Saadah Khudri, Nur; Nafis, Hasnan (Universitas Pahlawan Tuanku Tambusai, 2025)
The issue of gender equality in Islam is one of the central themes in contemporary Islamic studies. Normatively, Islamic teachings affirm the principle of justice and the equality of human dignity without gender discrimination. The Qur'an and Hadith contain values that support respect for women in spiritual, social, and political spheres. However, in practice, the application of gender equality in contemporary society often faces challenges, ranging from cultural conservatism to excessive liberalism. This paper analyzes the principles of gender equality in Islam and their application in the modern social context, emphasizing the importance of maintaining balance to avoid falling into extreme mindsets that contradict Islamic values themselves. A proportional approach between normative texts and social realities is necessary to actualize a form of gender equality that is just, ethical, and not excessive. Thus, Islam remains relevant in building a society that equally respects the dignity of both men and women without compromising the principles of Sharia.